2016
DOI: 10.1111/tme.12300
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag after allogeneic haematopoietic cell transplantation in a case of poor graft function and systematic review of the literature

Abstract: The use of eltrombopag or other TRAs to treat poor graft function after allogeneic HCT is intriguing and warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 13 publications
(17 reference statements)
1
30
0
Order By: Relevance
“…Although these publications may suffer from publication bias of positive outcomes, overall they show promising results. [8][9][10][11][12][13][14][15] In this preliminary study in which we recruited 20 alloSCT recipients with posttransplant severe thrombocytopenia, we have tried to perform a careful and thoughtful descriptive analysis to emphasize the importance to keep working on improving the treatment in common and relevant post-SCT complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these publications may suffer from publication bias of positive outcomes, overall they show promising results. [8][9][10][11][12][13][14][15] In this preliminary study in which we recruited 20 alloSCT recipients with posttransplant severe thrombocytopenia, we have tried to perform a careful and thoughtful descriptive analysis to emphasize the importance to keep working on improving the treatment in common and relevant post-SCT complications.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, the reported experience on their use after alloSCT is currently limited. [8][9][10][11][12][13][14][15] In this study, we retrospectively evaluated TPOa efficacy and safety in 20 consecutive adult alloSCT recipients who received either romiplostim or eltrombopag as a compassionate use for treating severe thrombocytopenia postengraftment in alloSCT recipients, exploring the potential predictive factors of response in this cohort.…”
mentioning
confidence: 99%
“…The variable definition of response across the included studies makes interpretation and comparison of overall response rate difficult. For example, some studies defined response by freedom from platelet transfusion, 34 others by normalization of platelet count, [35][36][37] and others by a target platelet threshold of ≥50 000/µL. [38][39][40][41][42][43][44][45] The best approximation of the combined overall response rate for both agents was 71% (Figure 1).…”
Section: Clinical Studies Of Tro Mimetics After Allogeneic Hctmentioning
confidence: 99%
“…Twelve reports of 119 patients with prolonged thrombocytopenia post HCT were included in this review as shown in Table 3. [34][35][36][37][41][42][43][44][45][58][59][60] An additional 67 patients were treated with eltrombopag in articles that reported outcomes combined with romiplostim as shown in Table 4. [55][56][57] Two reports included pediatric patients.…”
Section: Eltrombopag For Delayed Thrombocytopenia Following Hctmentioning
confidence: 99%
“…There is a continuing search for adjunctive therapy that may improve the outcome of HSCT. The thrombopoietin mimetic Eltrombopag has been used to enhance graft function and stimulate platelet production after allogeneic HSCT (Dyba et al, ).…”
mentioning
confidence: 99%